E-Module Development: Learning Innovation to Increase Students’ Understanding of Building Materials Science - Afrilia Fatmawati, Della; R Eka Murtinugraha (Journal of Engineering Education and Pedagogy, 2024)
This study aims to develop e-module-based teaching materials for building materials science courses in the Building Engineering Education Study Program, Faculty of Engineering, State University of Jakarta. The method used in this research is Research and Development (R&D) with the 4D model consisting of Define, Design, Develop, and Disseminate. This research begins with the collection of needs analysis data through questionnaires, product design, product validation, limited product trials, and ends with user assessment of the products that have been developed. The results of material expert validation on e-modules were declared very feasible by obtaining a percentage of 89.39%, and media expert validation was declared very feasible with a percentage of 93.94%. The results of the limited trial on each e-module showed an increase in learning outcomes, and the e-module received a positive assessment from users by obtaining a percentage of 93.65% with a very feasible category. It can be concluded that e-modules can be used in learning building materials science courses in the Building Engineering Education Study Program, Faculty of Engineering, State University of Jakarta.